Poetry in Management Research - Simone Antonello, Cláudia; Paes Barreto Davel, Eduardo (Organizações & Sociedade, 2022)
Poetry can contribute to advance management research. Reflecting on poetry as a path to regenerate management research lets us understand the ways of researching and the constitution of the researcher. Poetry is a way to start the construction of meaning and, at the same time, a coping mechanism, a way of re-existing not to de-exist. The poetic representation of lives is not an end in itself. The goal is political: to change the way we think about people and their lives in organizations using the poetic format. The researcher-poet makes the world visible from new perspectives and understandings, evidencing a political-ethical responsibility regarding the poetic. Poetry can move beyond prescribed ways of reading, writing, understanding, and ‘doing’ organizations and management, connecting itself to ethical considerations of voice and power dynamics.